Therapeutic role of corticosteroids in COVID-19: a systematic review of registered clinical trials - Reshma Raju; Prajith V.; Pratheeksha Sojan Biatris; Sam Johnson Udaya Chander J. (SpringerOpen, 2021)
Abstract Background In March 2020, the World Health Organization declared the coronavirus disease 2019 as a global pandemic. Though antiviral drugs and antimalarial drugs are considered treatment options for treating coronavirus disease 2019 (COVID-19), no specific antivirals are currently available for its treatment. Efficient use of drug discovery approaches including repurposing or repositioning of drugs used in the treatment of severe acute respiratory syndrome coronavirus (SARS-CoV) and the Middle East respiratory syndrome coronavirus (MERS-CoV) is considered recently. The widespread application of corticosteroid therapy in COVID-19 should be backed with careful documented pragmatic research of its use in this context. Main body This article aims to analyze various trials registered across the globe providing an overall picture of the use of corticosteroids in the treatment of COVID-19. An extensive search was conducted on the clinical trial registries around the world to identify all the trials reporting information regarding the use of corticosteroids in COVID-19. Our initial search returned 231 trials, out of which 60 trials were finally included in the analysis. Fifty-six studies were interventional trials, and all the trials had clearly defined primary and secondary outcomes of interest, of which only 11 trials had evaluation of respiratory rate as one of their outcomes. Conclusion Few preliminary trial findings show promising results and recommend the use of methylprednisolone and dexamethasone in the severe form of the disease; however, there is insufficient data to prove its benefits over its risks. Routine use of corticosteroids should be favored only after a better insight is obtained, with the completion of these trials.